The Key to Pro-Business Public Services Success: An Analysis of Motivation and Job Satisfaction - Melanda Wulandari; Asep Jamaludin; Nandang Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study aims to examine the influence of motivation and job satisfaction on employee performance at the One-Stop Investment and Integrated Services Office (DPMPTSP). The research employs a quantitative method with a survey approach. The sample consists of the entire population of employees at DPMPTSP, totaling 50 individuals. Primary data were collected through questionnaires. The data were analyzed using multiple regression with the assistance of SPSS version 26.0. The results indicate that employee motivation at DPMPTSP falls under the "very good" category. Job satisfaction is also assessed as "very good," while employee performance is categorized as "good." Both motivation and job satisfaction have a significant joint effect on employee performance. Furthermore, motivation has a partially significant effect on employee performance. Likewise, job satisfaction also shows a positive and significant partial effect on employee performance.